2013
DOI: 10.1186/1477-7819-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of chemosensitivity prediction using quantitative dose–response curve classification for highly advanced/relapsed gastric cancer

Abstract: BackgroundThe use of standard chemotherapy regimens has changed the application of chemosensitivity tests from all chemotherapy-eligible patients to those who have failed standard chemotherapy, which includes patients with highly advanced, relapsed, or chemoresistant tumors.MethodsWe evaluated a total of 43 advanced primary and relapsed gastric cancers for chemosensitivity based on drug dose response curves to improve the objectivity and quality of quantitative measurements. The dose response curves were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Consistent with previous studies [ 35 – 39 ], we found that Gli2, FoxM1 and KIF20A are highly elevated in primary human HCC samples. However, our analysis of 210 HCC cohort samples also revealed that the expression of these genes is positively correlated with each other.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous studies [ 35 – 39 ], we found that Gli2, FoxM1 and KIF20A are highly elevated in primary human HCC samples. However, our analysis of 210 HCC cohort samples also revealed that the expression of these genes is positively correlated with each other.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, free radicals are well known to play a major role in the development of oxidative stress that can lead to many illnesses including cardiovascular diseases, diabetes, inflammation, degenerative diseases, and cancer [ 26 ]. Nitric oxide (NO), a molecule playing a crucial role in inflammatory response, can react with free radicals such as superoxides to produce peroxynitrites that can cause irreversible damage to cell membranes leading to the promotion of tumor growth and proliferation [ 27 ]. In addition, natural inhibitors of lipoxygenases have been shown to suppress carcinogenesis and tumor growth in a number of experimental models [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, the management of GCTs has been curettage followed by filling with bone cement [7,19] . However this has been associated with high recurrence rates.…”
Section: Giant Cell Tumour Of Bonementioning
confidence: 99%